From copula to fertilization: The reproduction of primitive crab Hypoconcha parasitica (Linnaeus, 1763) (Podotremata: Dromiidae). Issue 11 (8th April 2022) - Garcia Bento, Maria Alice; López Greco, Laura S.; Mantelatto, Fernando L.; Zara, Fernando José
Abstract: This study describes the mating behavior of Hypoconcha parasitica under laboratory conditions highlighting the spermathecal morphology and focusing on the seminal fluid storage and release of spermatozoa. The pairs were kept in aquaria where the mating behavior was recorded and described. The spermathecae of the female were analyzed using scanning electron microscopy, X‐ray micro‐CT, histology, and histochemistry. No pre‐ or post‐copulatory mate guarding was observed in H. parasitica . The sperm transfer occurred with each pair maintaining the protection shield (bivalve shell) on their dorsum. The pair of spermathecae is covered exclusively by the cuticle, following the Podotremata pattern. Many muscle fiber bundles are attached to the cuticular wall facing toward the cephalothorax cavity, especially covering the lateral and slightly dorso‐anterior region toward the apodeme of Sternite 7. The spermathecal organization indicates that the process of sperm release during fertilization occurs through muscular action exerted by the female on the wall of the chamber. Thus, the musculature distribution in Hypoconchinae distinguishes them from described for other Podotremata such as Homolidae, which shows the musculature associated with the spermathecae aperture. Like the Homolidae, the first pleopod in H. parasitica seems to take part in the transfer/ movement of spermatozoa and oocytes between the sternum and abdomen, which forms a temporary chamber where fertilization occurs. In conclusion, the spermathecal morphology and associated structures bring new insights to the mechanisms involved in the sperm storage and fertilization of primitive crabs and how the Dromiidae spermatheca perform a new pattern among the poorly studied Podotremata.